The similarity of metaphorical concepts in Hassan Al-Bassam's poetry and its impact on the pictorial system - م.د عادل عبد الكاظم جويد (مجلة اداب ذي قار, 2023)
Metaphor occupies a significant space in the Arab and Western rhetorical and critical field. On the one hand, it is an aesthetic stylistic feature concerned with embellishing and improving discourse. The metaphor has spread in the poetry of our poet in such a way that it allows us to count it as an artistic feature that enters the number of pictorial features that are no less important than analogy, so he multiplies it in praising him and lamenting him. , and creativity.